1995
DOI: 10.1177/019262339502300203
|View full text |Cite
|
Sign up to set email alerts
|

Basic Principles of Pharmacokinetics

Abstract: Pharmacokinetics may be defined as what the body does to a drug. It deals with the absorption, distribution, and elimination of drugs but also has utility in evaluating the time course of environmental (exogenous) toxicologic agents as well as endogenous compounds. An understanding of 4 fundamental pharmacokinetic parameters will give the toxicologic pathologist a strong basis from which to appreciate how pharmacokinetics may be useful. These parameters are clearance, volume of distribution, half-life, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 9 publications
2
94
0
Order By: Relevance
“…Kinetic studies have confirmed that the half-life of red cell folate closely matches the half-life of red blood cells, 60 days [ 45 ]. Kinetic principles dictate that following a change in intake it will take four half-lives for blood concentrations to reach 94% of the new steady state levels [ 46 ]. Thus, red cell folate will change relatively slowly after an alteration of intake and may not reach steadystate levels until after 35 weeks.…”
Section: Kinetic Differencesmentioning
confidence: 85%
“…Kinetic studies have confirmed that the half-life of red cell folate closely matches the half-life of red blood cells, 60 days [ 45 ]. Kinetic principles dictate that following a change in intake it will take four half-lives for blood concentrations to reach 94% of the new steady state levels [ 46 ]. Thus, red cell folate will change relatively slowly after an alteration of intake and may not reach steadystate levels until after 35 weeks.…”
Section: Kinetic Differencesmentioning
confidence: 85%
“…Equations used are standard pharmacokinetic equations [9,12,13] based on a one compartment model considering immediate absorption to estimate the average (C ave , Eq. 1), minimum (C min , Eq.…”
Section: Inverse Dose-to-man (D2m) Predictionmentioning
confidence: 99%
“…Pharmacokinetics, by the quantitative study of the processes that take place depending on time, offers a better understanding of the relationship between the given/administered dose and the pharmacological effect [15]. The compartmental modeling approach of pharmacokinetics consists in describing the processes that the administered drug is subjected to in the body, depicted as an entity divided into distinct compartments with different properties and specific affinities for the drug or drug metabolites [16].…”
Section: Introductionmentioning
confidence: 99%